Методы оценки и выбора поставщиков - Kondratovich I. I. (Economic science today: theory and practice, 2016)
This article describes the stages of the selection of suppliers. We describe the criteria and methods for the analysis of the most appropriate option for the company.
Keywords: этапы; stages; выбор поставщика; методы выбора; балльный метод; матричный метод; метод сравнений; оценка поставщиков; критерии выбора; supplier selection; selection methods; point rating method; matrix method; Comparison of methods; supplier evaluation; stoimotnyh method of cost-estimates; Criterias of choice; метод затратно-стоимостных оценок